Confiscarea în cauzele de trafic de ființe umane și proxenetism [Articol] - Reniţă, Gheorghe (CEP USM, 2020)
Confiscation in the criminal case could concern movable and/or immovable goods. At the same time, the confiscation of property must be considered an interference with property rights.However, property rights are not absolute, but relative. It may be subject to limitations, which must be provided by law, to pursue a legitimate purpose and to be proportionate to the purpose pursued. Therefore, by balancing, on the one hand, the property right, and, on the other hand, the imperative of preventing and combating crimes of human trafficking and pimping, as a rule, the former must give in to the latter.
CONFISCATION IN THE CASES OF HUMAN TRAFFICKINGAND PIMPING
Keywords: confiscation; property rights; human trafficking; pimping; confiscare; trafic de fiinţe umane